'The jobs all go to foreigners': a critical discourse analysis of the Labour Party's 'left-wing' case for immigration controls - Bates, David (Critical discourse studies, 2023)
This paper critically examines how senior figures in the UK Labour Party and wider labour movement discussed the topic of immigration in the immediate aftermath of the UK's vote to leave the European Union in 2016. Influenced by the Discourse Historical Approach, the paper is based on an analysis of 86 public interventions by Labour figures, over a 6-month period, delivered in speeches, articles and essays. The paper examines argumentative strategies adopted by Labour figures - including Members of Parliament, advisors and trade union leaders - who called for stronger immigration controls from an avowedly 'left-wing' perspective. Foregrounding their commitment to progressive politics, Labour politicians argued that restricting the number of migrants entering Britain was democratic, anti-racist and an expression of the Labour Party's commitment to the interests of working-class people. Nevertheless, it is the contention of this paper that the Labour Party's rhetoric tapped into right-wing populist discourses which constructed immigration as a threat to the racialised privileges of a 'white' working class.